BELAJAR MEMBUAT SLIME BERSMA ANAK – ANAK DALAM MENGISI KEGIATAN BELAJAR DARING DI DESA KIRINGAN, BOYOLALI - MARNI; ALEAN KISTIANI H.S; DONNA SETIAWATI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Community Service Program (KKN- Kuliah Kerja Nyata) is a forum that is given to Universitas Boyolali students and students a masterpiece. Creating students who are able to play a role in society, as well as making students close to the community to establish Islamic Ukhuawah, students who are the highest level of education have a very important role in the survival of the state. Students can act as actors of Agents of Change in a pluralistic society. A forum given by UBY in the form of KKN activities is an important step for a student to practice the application of knowledge from lecture halls into a more real world with pro-contract that can occur in the process. During the Covid-19 pandemic there were many changes in healthy lifestyle that had to be implemented. Especially changes in the way students learn, both elementary school and university students, all use online technology. Due to online learning activities, a lot of elementary and kindergarten students in my village are bored. Therefore, the writer wants to give space and time to fill the boredom by learning and playing to make slime. By playing and learning, the children look happy and feel proud of their work. This KKN activity is located in Kiringan village, Boyolali District, Boyolali Regency. Precisely at RT 1 RW 6. During the community service, the writer also followed routine activities that had been going well in the village such as posyandu and regular group meetings of women.